2022
DOI: 10.1037/cns0000266
|View full text |Cite
|
Sign up to set email alerts
|

An insula view of predictive processing in hypnotic responses.

Abstract: The experience of being hypnotized is closely linked to changes in bodily experience or interoceptive sensations. Progress in the neuroscience of hypnotic motor suggestions, both ideomotor and challenge, implicates changes in the comparison processes between predicted (expected) and actual proprioceptive consequences of current action models and plans in behavioral and experiential response to these suggestions. These findings are interpreted as a form of active inference, minimizing prediction errors in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Delayed intention awareness has also been observed in FND (Baek et al, 2017;Jungilligens et al, 2020) and conceptually similar results have been reported in those displaying high dissociative absorption (Bregman-Hai et al, 2020). An alternative interpretation of this association can be drawn from predictive processing models of FND (Edwards et al, 2012;Keynejad et al, 2019), and hypnosis (Jamieson, 2021;Martin & Pacherie, 2019). Within the context of predictive processing, highly suggestible individuals may possess an enhanced capacity to form precise symptom priors that override somatic and psychological states, resulting in aberrant motor, cognitive, and perceptual phenomena.…”
Section: Implications For the Mechanisms Underlying Dissociative Psyc...mentioning
confidence: 53%
“…Delayed intention awareness has also been observed in FND (Baek et al, 2017;Jungilligens et al, 2020) and conceptually similar results have been reported in those displaying high dissociative absorption (Bregman-Hai et al, 2020). An alternative interpretation of this association can be drawn from predictive processing models of FND (Edwards et al, 2012;Keynejad et al, 2019), and hypnosis (Jamieson, 2021;Martin & Pacherie, 2019). Within the context of predictive processing, highly suggestible individuals may possess an enhanced capacity to form precise symptom priors that override somatic and psychological states, resulting in aberrant motor, cognitive, and perceptual phenomena.…”
Section: Implications For the Mechanisms Underlying Dissociative Psyc...mentioning
confidence: 53%
“…Although a wealth of evidence indicates that response expectancies are a reliable predictor of responsiveness to (hypnotic) suggestions, there are ongoing questions regarding the magnitude of these effects as well as the underlying mechanisms (for reviews, see (Lynn et al, 2022;Lynn et al, 2008;Terhune et al, 2017). Similar ideas are present in more recent theories of hypnotic suggestion (Jamieson, 2018(Jamieson, , 2022Martin & Pacherie, 2019) embedded within the predictive coding framework (Clark, 2013;Friston, 2010). This framework views the brain as a hierarchical Bayesian inference machine that works to minimize the discrepancy between predictions and sensory evidence while weighting these factors based on their respective confidence levels (precision).…”
Section: Response Expectancy and Predictive Coding Theoriesmentioning
confidence: 86%
“…But how is it that hypnotic suggestion, that is, high-level, top-down, cognitive instructions, can so dramatically alter relatively low-level, bottom-up processes, such as the functioning of comparator processes in the motor system? One way to explain these changes is in terms of predictive coding or ideomotor frameworks (Dogge, Custers, & Aarts, 2019; Jamieson, 2016, 2022; Martin & Pacherie, 2019; Woody & McConkey, 2003). Woody and McConkey (2003) provided an account of how this might occur, based on Friston’s (2002) “predictive architecture” model of sensory processing.…”
Section: Discussionmentioning
confidence: 99%